EVOKED POTENTIALS IN CHILDREN WITH PAROXYSMAL DISORDERS - V. B. Voitenkov; E. Yu. Gorelick; N. V. Skripchenko; A. V. Klimkin (Эпилепсия и пароксизмальные состояния)
In this review we discuss clinical significance of using evoked potentials in children with epilepsy and related disorders. This approach has been commonly adapted for practice in pediatric epileptology. In most cases, it serves a neuromonitoring tool to assess the effectiveness of a therapy program and / or its side-effects. In addition, the method of evoked potentials is helpful in testing the central inhibition and excitation balance in different forms of epilepsy. In this respect, we also take a look at the impact of epileptic activity on the function and development of brain regions. The method of evoked potentials may be used for localization of epileptic lesions in children suffering from focal epilepsy. Given the variety of existing modalities of evoked potentials, their safety, painlessness and neuromonitoring qualities, we recommend to expand the use of these techniques in pediatric patients with paroxysmal disorders.